2010
DOI: 10.1038/embor.2010.114
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E‐cadherin to disrupt intercellular adhesion

Abstract: Mammalian and prokaryotic high-temperature requirement A (HtrA) proteins are chaperones and serine proteases with important roles in protein quality control. Here, we describe an entirely new function of HtrA and identify it as a new secreted virulence factor from Helicobacter pylori, which cleaves the ectodomain of the cell-adhesion protein E-cadherin. E-cadherin shedding disrupts epithelial barrier functions allowing H. pylori designed to access the intercellular space. We then designed a small-molecule inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
326
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 267 publications
(339 citation statements)
references
References 24 publications
6
326
0
6
Order By: Relevance
“…We have previously shown that E-cadherin represents an important substrate for HpHtrA allowing paracellular transmigration of H. pylori across the polarized epithelial cell barrier (4). Having established that recombinant HtrAs from various Gram-negative pathogens were indeed proteolytically active, we next tested whether different HtrAs also target E-cadherin as a substrate in vitro or on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that E-cadherin represents an important substrate for HpHtrA allowing paracellular transmigration of H. pylori across the polarized epithelial cell barrier (4). Having established that recombinant HtrAs from various Gram-negative pathogens were indeed proteolytically active, we next tested whether different HtrAs also target E-cadherin as a substrate in vitro or on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…HtrA-mediated cleavage of E-cadherin facilitated the loss of the adherence junction complex, leading to the disruption of the epithelial barrier function in response to H. pylori infection (4).…”
mentioning
confidence: 99%
“…The substrate specificity of HtrA proteases ranges from that of DegS in Escherichia coli, which is highly selective for digestion of RseA as a key step in initiating the envelope-stress response (12), to that of proteases such as DegP in E. coli (13) and DegQ in Legionella (14) and homologues in Synechocystis (15), which are broadly active against unfolded proteins in which hydrophobic regions are exposed to solvent. In addition to such endogenous substrates, HtrA proteases have recently been characterized from the pathogens Helicobacter pylori (16) and Campylobacter jejuni (17) that cleave host proteins to promote bacterial migration across epi-thelial barriers. A shared feature among the HtrA proteases appears to be their ability to form oligomers starting at the level of trimers (14, 15, 18 -25), which in some cases are then able to assemble and disassemble dynamically to produce large structures consisting of 24 or more monomers.…”
mentioning
confidence: 99%
“…In consistency, htrA mutants of many pathogens show attenuated virulence [128][129][130][131]. Intriguingly, a novel role has recently been identified for HtrA of Helicobacter pylori and Campylobacter jejuni: HtrA was found to be secreted during infection and acts as a virulence factor that specifically cleaves the extracellular domain of E-cadherin on infected gastric epithelial cells [132][133][134][135]. As a consequence, the mucosal integrity of the epithelium is destroyed, and the bacteria are enabled to transmigrate across the epithelial layer where they induce severe inflammation and cause disease.…”
Section: Thermo-regulated Disassembly Of Oligomeric Protein Sensorsmentioning
confidence: 99%
“…Class C proteins bind to plasma proteins at low temperatures as coiled coils; homodimers disassemble at 37°C; C-repeats seem to be the thermosensitive unit [122] Helicobacter pylori Campylobacter jejuni HtrA Secreted virulence factor, cleaves E-cadherin as protease; forms homooligomers and is fully induced at 37°C, disassembly of HtrA oligomers at low temperatures [132,133,136] Yersinia spp. RovA…”
Section: Salmonella Enterica Tlpamentioning
confidence: 99%